EFFECT OF GENDER ON THE CONSUMER’S CHANNEL SELECTION OF FAST FASHION APPAREL PRODUCTS - Yu Liu; Wenbo Shan; Fenfen Yu (European Scientific Journal, ESJ, 2015)
This paper takes the consumers of fast fashion clothing products as research subjects, and EMB model as logistic basis to compare and analyze the preference of male and female on three channels including Internet, mail order catalogue (telephone ordering) and entity shops in the whole purchasing process (including need recognition, information search, alternative evaluation, purchase, and after purchase evaluation) with the influential factors by means of questionnaire. Throughout the research, it is concluded that the consumers of fast fashion clothing products of different gender consumers have difference in preference on the channels in different stages of purchasing decision. It has great reference significance that Fast Fashion Costume makes the effective market strategies according to gender difference.